Can gender differences in the educational performance of 15-year old migrant pupils be explained by the gender equality in the countries of origin and destination? - Jaap Dronkers; Nils Kornder (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
We try to explain the differences between the performance (in both reading and math) of 8430 15-year-old daughters and 8526 15-year-old sons in 17 Organisation for Economic Cooperation and Development destination countries across Europe and Oceania with the PISA 2009 data from 45 origin countries or regions. In addition to the level of societal gender equality of the origin and destination countries (the gender empowerment measure, or GEM) we use macro indicators of the educational systems, economic development, and religions of the countries of origin. We find that migrant daughters from countries with higher levels of gender equality have higher reading scores than comparable migrant sons (but this is not the case for math scores). In addition, the higher the level of gender equality in the destination countries, the lower the reading and math scores of both the male and female migrants' children in their destination countries. Further analyses suggest that the difference between the levels of gender equality, rather than the levels themselves, of the origin and destination countries explains more of the educational performance of both female and male migrant pupils. Our results also show that the low level of gender equality in Islamic origin countries is a sufficient explanation of the low educational performance of Islam male and female migrants' pupils. Finally, migrants' daughters seem to perform slightly better educationally than comparable migrants' sons.
Keywords: 330